안드로이드 스마트폰 기반의 원격 IPMC 제어시스템 구현 - 김관형; Kim, Gwan-Hyung (한국정보통신학회논문지, 2013)
Recently, Ionic Polymer Metal Composite (IPMC) systems receive great attention in the fields of the medical and biomedical Engineering because of several merits in terms of new actuators and sensors and fuel cell materials. When the voltage is excited to IPMC system, it moves. Conversely, if there are any movement on the IPMC, the IPMC has charge voltage by the internal properties. Therefore the IPMC can be used as a motion sensor or force sensor. In this paper, we identify characteristics of the IPMC and control its movements from remote locations by the smart-phone system based on visual information for monitoring. Additionally, control of movements of the IPMC is realized by transmit motion commands using the smart-phone system with the blue-tooth communication. Unfortunately, there are some deficiencies to perfectly attain physical properties of the IPMC systems from our experiments in this paper. However, in its utilization point of view, we demonstrate that the IPMC has some potentials as new sensors, actuators, and fuel cells. 최근 의료 및 생체공학 분야의 액추에이터(actuator)와 센서 및 연료전지로 활용할 수 있는 새로운 재료인 IPMC(Ionic Polymer Metal Composite)에 대한 관심이 높아지고 있다. 이러한 IPMC의 특징은 센서(sensor)와 액추에이터(actuator)의 성질을 동시에 가지는 있는 특이한 성질을 가진 복합재료로서 IPMC에 전압을 가하면 움직임이 생기며, IPMC에 움직임이 발생하면 IPMC 내부에 전압이 충전되는 성질이 있어 모션 센서나 힘 센서로도 활용할 수 있다. 본 논문에서는 이러한 IPMC에 대한 몇 가지 특성을 파악하고 IT 기술인 스마트폰의 연계하여 원격지에서 IPMC의 동작을 제어할 수 있도록 시스템을 구성하였다. 또한, 스마트폰을 기반으로 하여 영상정보를 전송하여 모니터링 하도록 하였다. IPMC의 동작제어는 스마트폰의 블루투스를 이용하여 동작명령을 전송하도록 시스템을 구현하였다. 본 논문의 실험 및 구현으로부터 IPMC 물성에 대한 정확한 분석은 부족하지만 향후 IPMC의 활용에 있어서 IT 기술과의 융합을 통하여 센서, 액추에이터, 연료전지 등과 같은 분야에 적극 활용할 수 있음을 확인할 수 있었다.